Propriedades ópticas e térmicas da oleína de palma - NUNES, Edson Carlos de Barros (Universidade Federal do Pará, 2014)
We used an experimental methodology to investigate optical and thermal properties of palm olein (PO), the liquid fraction of the palm oil (Elaies guineensis) obtained by natural fractionation with physical properties very different of the oil. In a first approach, we study both the absorption and emission spectra monitoring the modifications in the spectral curves caused by the increase of the concentration of β-carotene diluted into PO. This procedure allowed to find the molar absorption coefficient of the β-carotene (ε = 920,802 L.mol-1.cm-1). This value is very small compared with β-carotene diluted in pure solvent like benzene or n-hexane. Measurements of the absorption spectra of β-carotene in pure hexane allow us to measure ε = 117.900 L.mol-1.cm-1, only 18% below of that reported in the literature. In a second approach, the absorption spectra were used to measure the absorption coefficient of the PO, A = 0,028 cm-1 at 532 nm, the wavelength of a laser used as excitation source to investigate thermal properties of the PO by thermal lens spectroscopy. In this sense, was measured too the thermal coefficient of the refractive index of the PO, dn/dt = -3,821 x 10-4°C-1, using an Abbé’s refractometer coupled to a thermal bath with controlled temperature. These results associated with the aberrant model for thermal lens spectroscopy studies, allowed to measure the thermal diffusion coefficient, D = 2,19 ± 0,11 x 10-4 cm2/s, and the thermal conductivity, k = 5,96 ± 0,08 W/m°C, from the palm olein. Although the thermal properties measured for the PO not been knowledge in the literature yet, one observes that they has the same order of magnitude of the similar thermal properties measured in other vegetable oils reported in the literature.